2008
DOI: 10.5271/sjweh.1291
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of aluminum in aluminum welders and manufacturers of aluminum sulfate—impact on biological monitoring

Abstract: Riihimäki V, Valkonen S, Engström B, Tossavainen A, Mutanen P, Aitio A. Behavior of aluminum in aluminum welders and manufacturers of aluminum sulfate-impact on biological monitoring. Scand J Work Environ Health 2008;34(6):451-462. ObjectivesThe suitability of determining aluminum in serum or urine as a form of biological monitoring was critically assessed.Methods Airborne and internal aluminum exposure was assessed for 12 aluminum welders in a shipyard and 5 manufacturers of aluminum sulfate. Particles were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 16 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…Plasma collected from volunteers with no known Al exposure generally contains ≤ 2.7 μg/L (with an upper normal limit of ~6 μg/L), serum generally contains up to approximately 3 μg/L and urine generally contains approximately 1–9 μg/L. The Zeager et al (2012) conclusion is not consistent with others who have used blood and urinary Al to monitor HD patients (Pei et al 1992, 1995), Al welders and other industrial workers (DFG 2007, Riihimaki et al 2008, Riihimaki and Aitio 2012). …”
Section: Hepaticmentioning
confidence: 80%
“…Plasma collected from volunteers with no known Al exposure generally contains ≤ 2.7 μg/L (with an upper normal limit of ~6 μg/L), serum generally contains up to approximately 3 μg/L and urine generally contains approximately 1–9 μg/L. The Zeager et al (2012) conclusion is not consistent with others who have used blood and urinary Al to monitor HD patients (Pei et al 1992, 1995), Al welders and other industrial workers (DFG 2007, Riihimaki et al 2008, Riihimaki and Aitio 2012). …”
Section: Hepaticmentioning
confidence: 80%
“…In the study of Hull & Abraham on subjects exposed to welding fumes, the results showed that most of the particles were accumulated and the average diameter of the AL particles was 0.34 μm and there were also the singlet particles as small as 10 nm in diameter [27]. The toxicokinetic of AL in human by inhalation, which is the main route of exposure in occupational workplaces, has not received much attention [28]. It may be difficult to estimate the actual body burden due to the reabsorption of inhaled AL in the lung [9].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, they developed a method to collect, recover, and analyze Cr, Mn and Ni nanoparticles (metals that have been linked with severe health outcomes) generated during welding, separately from larger particles. Similarly, Riihimäki et al (Riihimäki et al, 2008) highlighted the impact of the particle size on toxicity: while aluminum metal and aluminum oxide are practically insoluble in water and are thus presumably poorly absorbed into living organisms, oxidized aluminum, contained in ultrafine particles, behaves differently, since some aluminum of the welding fume is rapidly taken up by the welder's lungs. It argues once again for the study of the finest fraction separately from its larger counterpart.…”
Section: Discussionmentioning
confidence: 99%